Development of the Game-based HOTS Assessment Instrument for Measuring Science Literacy Skills of Islamic Elementary School Students - Taufiq Satria Mukti; Melly Elvira; Zaharah Binti Hussin (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractScience literacy is an essential ability that elementary school students must possess. Science literacy can be developed in the learning and assessment process. Science literacy assessment requires a specific measuring instrument by prioritizing the HOTS cognitive concept. The development of science literacy assessment instrument adopted from the Djemari Mardapi Model aims to obtain the reliable instrument for gauging the studentsâ€™ science literacy skills. Involving experts, teachers as practitioners, and essential education experts, the assessment instrument was developed in the form of a game-based multiple-choice test with Quizizz. The instrument testing was conducted in grades 4, 5 and 6 of one of Islamic Elementary School in Malang Regency, Indonesia. The analysis of the instrument consisted of content validity and test reliability. The development results revealed that the instrument met the perfect content validity and the empirical test with a very high-test reliability value (0.89). The assessment process by Quizizz game showed that the students were very enthusiastic. Despite the promising results as shown in this study, it is still necessary to enhance the science literacy skills of students by familiarizing them with HOTS-based cognitive questions.Keywords: science literacy, HOTS game-based assessment, empirical validity.Â AbstrakLiterasi sains merupakan kemampuan esensial yang harus dimiliki siswa sekolah dasar. Literasi sains dapat dikembangkan dalam proses pembelajaran dan penilaian. Penilaian literasi sains memerlukan alat ukur khusus dengan mengutamakan konsep kognitif HOTS. Pengembangan instrumen asesmen literasi sains yang diadopsi dari Model Djemari Mardapi bertujuan untuk mendapatkan instrumen yang handal untuk mengukur kemampuan literasi sains siswa. Melibatkan pakar, guru sebagai praktisi, dan pakar pendidikan esensial, instrumen penilaian dikembangkan dalam bentuk tes pilihan ganda berbasis permainan dengan Quizizz. Uji coba instrumen dilakukan di kelas 4, 5 dan 6 salah satu Madrasah Ibtidaiyah di Kabupaten Malang, Indonesia. Analisis instrumen terdiri dari validitas isi dan uji reliabilitas. Hasil pengembangan menunjukkan bahwa instrumen memenuhi validitas isi sempurna dan uji empiris dengan nilai reliabilitas tes sangat tinggi (0,89). Proses penilaian dengan permainan Quizizz menunjukkan bahwa siswa sangat antusias. Terlepas dari hasil yang menjanjikan seperti yang ditunjukkan dalam penelitian ini, masih perlu untuk meningkatkan kemampuan literasi sains siswa dengan membiasakan mereka dengan soal-soal kognitif berbasis HOTS.Kata kunci: literasi sains, penilaian berbasis permainan HOTS, validitas empiris.